PENENTUAN KORELASI EMPIRIS LOKAL PERPINDAHAN PANAS PADA BAGIAN SEKTOR ELLIPS MODEL SUNGKUP AP1000 - Hermawan, Nanang Triagung Edi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Nuclear reactor technology is one application of the theory of nuclear physics by usingenergy generates from fission reaction in nuclear fuel. AP1000 reactor design applies containment surface cooling by natural air flow. Air flows at inner gap from bottom of concentric cylindrical ellipse sector part to upper of containment surface. Heat transfer characteristic on ellipse sector is very important to be known because in this part heat accumulation from cylindrical heat transfer is happened. Natural convection heat transfer could be represented by empirical correlation equation. Experimental studies have been done on AP1000 containment model proportion 1:40. The result of the experiment indicates that containment surface cooling in accident scenario couldbe happened optimally. Average temperatureof the outer surface of containment is 55.82 0C (well below re-crystallization point for SS-304, which is about 900 0C). The local empirical correlation from this experiment is Nux = 0,577Ra*0,2532, for Rayleigh numbers 7,51 x 105< Ra* < 7,08 x 1010. Keywords: AP1000 reactor, containment cooling, ellipse sector, and empirical correlation.